Clinical Evaluation of Three Restorative Materials Applied in a Minimal Intervention Caries Treatment Approach - Regia L. Zanata, PhD; Maria F. L. Navarro, PhD; Silvia H. Barbosa, DDS; Jose R. P. Lauris, PhD; (Blackwell Synergy, 2003)
This paper reports on a longitudinal evaluation of three materials (glass ionomer, zinc oxide-eugenol cement, and composite) employed in a minimal restorative intervention approach of 8 1 high caries-active pregnant women selected for a preventive oral health program in Brazil. The aim of the study was to evaluate the clinical behavior of the glass ionomer cement, currently indicated in programs for control of carious lesions